Hydrogen production by decomposition of methane and methanol mixture over Ni-Pd/Al2O3 - Awad, A. (Japan Institute of Energy, 2017)
Thermocatalytic decomposition of methane (TCD) is a promising method for producing hydrogen. However, the main concerns of this process are very high reaction temperature and fast deactivation of the catalyst. In this work, a positive approach has been made to minimize both effects by using Pd-promoted catalyst prepared by the co-precipitation and impregnation method. Pd has a high affiliation with carbon, thus instead of encapsulating Ni, it diffuses in promoter hence the catalytic lifetime is prolonged. EDX and XRD analysis confirmed the presence of NiAl2O4, Al2O3, Pd, and Ni. BET analysis depicts that the surface area is decreased as the amount of metal content impregnated on the support is increased. FESEM analysis shows the nano particles are synthesized while carbon nanofibers are produced as by-product. The highest conversion of CH4 was given by Cat 1 (24.7 wtNi-0.3 wtPd/Al2O3) i.e. 45.